Prescription Patterns of Antimicrobial Drugs in Hospitalized Patients in Tertiary Care Hospital of Kathmandu - Raut, Binod; Khadka, Anjan; Borah, Rabindra Nath (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Antimicrobial drugs are one of the most commonly prescribed drugs in hospital. Overuse and irrational use of antimicrobials is a key factor behind rapidly spreading antimicrobial resistance in microorganisms. Use of irrational and unnecessary antimicrobials remains common in the developing countries. This study was conducted to analyze the prescription pattern of antimicrobials in the department of internal medicine of tertiary care hospital. Methods: Antimicrobials are among the most commonly prescribed drugs in hospital. Overuse and irrational use of antimicrobials is a key factor behind rapidly spreading antimicrobial resistance in microorganisms. Use of irrational and unnecessary antimicrobials remains common in the developing countries. This study was conducted to analyze the prescription pattern of antimicrobials in the department of internal medicine of tertiary care hospital. Results: The mean duration of hospitalization among the study population was 5 days. Of the 460 medicines prescribed, mostly indicated for respiratory infections, and the most common antibiotic was from the group cephalosporin 209 (69.7 %). 55 % of prescriptions include only one drug, 39 % with two drugs and 6% with three or more than three drugs. Conclusion: The mean duration of hospitalization among the study population was 5 days. Of the 460 medicines prescribed, mostly indicated for respiratory infections, and the most common antibiotic was from the group cephalosporin 209 (69.7 %). 55 % of prescriptions include only one drug, 39 % with two drugs and 6% with three or more than three drugs.